Seeking Justice for Indonesian Children: The Juvenile Criminal Justice System in Indonesia in the Context of Criminal Justice Reform (Indonesian Journal of Advocacy and Legal Services, 2022)
Children who are in contact with law in Indonesia have their own characteristics and handling procedures through the Juvenile Criminal Justice System. Through Law Number 11 of 2021 concerning the Juvenile Criminal Justice System, the state tries to be present to protect children's rights, even though children are perpetrators of crimes. Handling criminal cases against children is certainly different from handling cases against adults, the handling of children is special because it is also regulated in separate regulations. Understanding of the process of handling children's cases, of course, there may still be some in the community who do not understand or understand, so that sometimes it gives rise to various assessments, even more fatal if there is a misjudgment that the handling of children, especially children in legal conflicts 5 get special treatment and there are also those who think that children cannot be punished even though it is not that far, it's just that the handling process is specifically regulated. This study aims to analyze the concept of justice for children in the Indonesian Child Criminal Justice System within the framework of Criminal Justice Reform. The method used in this study is a mixed method between empirical and normative studies. This method is used to answer the substance of justice contained in the Juvenile Criminal Justice System within the framework of criminal justice reform. The location of this research was specifically carried out in the city of Semarang, and several other cities as supporting material. Supporting data in this study were also obtained from various studies on the internet.